Digitalisierung und Weiterbildung Beiträge zu erwachsenenpädagogischen Forschungs- und Entwicklungsfeldern - Robak, Steffi; Asche, Eike; Kühn, Christian; Heidemann, Lena (Verlag Barbara Budrich, 2022)
How does digitalisation affect adult and further education? The book shows the range of research perspectives and fields of application. Starting from basic theoretical research approaches, specific subject areas as well as application-related projects for the design of media-supported teaching-learning concepts are taken up. The contributions are not limited to technology-centred topics, but show the relevance of educational research for the design of the digital transformation. An interdisciplinary field of research and application is developed that cannot do without well-founded perspectives on adult education.